DETERMINATION OF SUSTAINABLE BUSINESS FACTORS OF ISLAMIC BANKS IN INDONESIA - Siswanti, Indra (The International Journal of Accounting and Business Society, 2019)
The objective of the study is to test and analyze the influence of corporate intellectual capital and company size on sustainable business through financial performance as a mediating variable. The data used was secondary data of financial and annual reports for 2010-2018 period. The population of this study was 9 (nine) Islamic Banks, and the samples used were saturated sampling, thus the sample used was all the 9 (nine) Islamic Banks. The data processing method used is Partial Least Square (PLS). The results of the study found that intellectual capital has a significant effect on financial performance, company size  has a significant effect on financial performance, where as intellectual capital has no effect on sustainable business. The study  found that financial performance has a significant effect on sustainable business. Financial performance has a full mediating influence of intellectual capital on sustainable business, and financial performance has a partial mediating influence of company size on sustainable business. Keywords:  Intellectual Capital, Company size, Financial Performance, and Sustainable Business